Flussbettveränderungen in rezenter Zeit: Ein Beitrag zur Morphologie der Flußsohle von Flachlandflüssen am Beispiel der Elbe - Gierloff-Emden, Hans-Günter (ERDKUNDE, 1953)
Using the records of the Wasserstraßenamt Hamburg for the period 1940 to 1949, precise isobathic maps of a section of the lower Elbe were constructed on the basis of over 10,000 soundings. These maps were used to determine and investigate in detail the changes in the river bed over ten years for the ten kilometre long section of the Elbe near Geesthacht. The following conclusions were reached. The main current, which is used as the navigation channel, swings to and fro in its own bed. In consequence sandbanks and potholes are formed in regular sequence; they do not change from one side of the river to the other, but, retaining their arrangement with each other, move about 300 metres downstream each year. The mean depth is 2 metres; the potholes reach a depth of up to 9 metres. The extremes of very large and very small cross sections of the water, as well as the extreme depths, have declined during this period and there is a tendency towards equalization. The differences of width and depth from cross section to cross section have also declined considerably. With reference to the datum level of 1929 the Elbe has increased its capacity on this ten kilometre stretch by a quarter of a million eu. m. during these ten years. This is equivalent to an average annual erosion of 24,760 eu. m.